Metal-rich heterostructure of Ag-doped FeS/Fe2P for robust hydrogen evolution. (1st June 2022) - Li, Meng-Xuan; Zhou, Ya-Nan; Dong, Yi-Wen; Liu, Xin; Luan, Ren-Ni; Liu, Bin; Zeng, Jing-Bin; Chai, Yong-Ming; Dong, Bin
Abstract: The transition metal phosphides (TMPs) with highly active and low-cost are imperative electrocatalysts for hydrogen evolution reaction (HER). In particular, metal-rich interface engineering of iron phosphide could effectively modify the active sites for HER and accelerate the charge transfer, thus achieving the promoted efficiency. Herein, we report metal-rich heterostructure of Ag-doped Fe2 P shell attached to FeS core on Fe foams (FeS/Fe2 P–Ag@IF) for HER, which are synthesized by a simple hydrothermal method with subsequent low-temperature phosphorization. Notably, the phosphorization process simultaneously achieves the partial conversion of FeS to Fe2 P, and complete reduction of Ag2 S to Ag. Furthermore, the metal-rich structure of Fe2 P increases the active sites for hydrogen adsorption, which consequently contributes to hydrogen evolution. Simultaneously, the successful doping of metallic Ag enhanced the electroconductivity and the stability of the electrocatalyst. Benefiting from the ternary synergistic effect at FeS/Fe2 P–Ag@IF and metallic Ag doping, the optimal Ag-doped FeS/Fe2 P electrocatalyst exhibits a low overpotential of 214.9 mV at 100 mA cm −2, even surviving at this large current density with long-term stability. This promising strategy involving metallic Ag doping may be a suitable option for the development of iron-based metal-rich phosphides heterostructured for HER. Graphical abstract: Image 1 Highlights: Phosphorylation process converts FeS partially to Fe2 P and Ag2 S completely to Ag. The metal-rich structure of Fe2 P increases the active sites for hydrogen adsorption. Ag doping effectively modulates the electronic structure and improves stability. Strong electronic interactions of metal-rich Ag-doped FeS/Fe2 P enhance the HER.